Thyroid Dysfunction among Greek Patients with Type 1 and Type 2 Diabetes Mellitus as a Disregarded Comorbidity - Maria E. Barmpari; Maria Kokkorou; Anastasia Micheli; Irene Alexiou; Elefteria Spanou; Marina Noutsou; Anastasia Thanopoulou (Journal of Diabetes Research)
Introduction. The aim of this study was to determine the prevalence of thyroid dysfunction in Greek patients with type 1 (T1DM) and type 2 (T2DM) diabetes mellitus as well as its possible relations to glycaemic control and to diabetic complications. Methods. A total of 1015 patients, consecutively followed in the Outpatient Diabetes Center, were studied. Anthropometric and biochemical measurements, occurrence of diabetes complications, and classical comorbidities were assessed. Average HbA1c of the previous year was calculated. Wellbeing was determined, using a 10-point optimal scale. All the above parameters were compared between subjects with or without thyroid disease. Results. All patients were euthyroid at the time of the study, either on thyroid medications or not. Hypothyroidism occurrence did not differ between T2DM and T1DM patients (37.1% versus 43.5%, p>0.05). Nodular goiter was observed more frequently in T2DM patients (34.1% versus 18.8%, p<0.05). T2DM patients with hypothyroidism compared to those without hypothyroidism had higher HbA1c (7.27% versus 6.98%, p<0.01), TChol (184.97 mg/dl versus 168.17 mg/dl, p<0.001), and higher HDL-Chol (51.28 mg/dl versus 46.77 mg/dl, p<0.01). T2DM patients without hypothyroidism had a better wellness feeling (7.5 versus 5.3 points, p<0.01). Conclusions. Screening for thyroid disease among T2DM patients should be routinely considered, as it is found to be an additional commorbidity. If it remains undiagnosed, it could aggravate the clinical course of the disease.